الصراع الحضاري بين الإسلام والغرب -إشكالية المفهوم - مرسدي, امال (University of Eloued جامعة الوادي, 2023)
ملخص:صراع الحضارات حالة لعلاقات دولية متوتّرة قائمة على أساس العداء و التّصادم و التّفاعل السّلبي والمنافسة العنيفة، بعيدا عن التّعايش السّلمي والتّفاهم، وهو سر من أسرار الكون، ومعناه في الإسلام التّدافع الحضاري الذي ليس مفهومه محو الآخر من الوجود، كما هو في الحضارة الغربية، بل هدايته إلى الحقّ، حتّى إن هاجمه أو حاول منع وصوله قُوتِل؛ أي: أنّه صراع دائم بين الحقّ والباطل والخير والشّر، وغالبا ما يهدف الصّراع الحضاري الغربي للقضاء على الإسلام والحدّ من انتشاره، والإبقاء على تخلّف المسلمين وتفرّقهم، فضلا عن البقاء في الرّيادة المزعومة والتّقدم المادي الحيواني الزائل ولو بعد حين. Abstract:The clash of civilizations is a state of tense international relations based on hostility, collision, negative interaction and violent competition, far from peaceful coexistence and understanding. It is one of secrets of the universe, and its meaning in Islam is the civilizational scamble , whose concept is not the erasure of the other from existence ,as the case is in western civilization, but rather. guiding him to the truth, so that if he attacked him or tried to prevent his arrival, he would be killed; That is a permanent struggle between right and wrong, good and evil, and the Western civilizational struggle often aims to eliminate Islam and limit its spread, and to maintain the backwardness and disunity of Muslims, as well as to remain in the alleged leadership and fleeting animal material progress, even after a while
مقال
Keywords: الكلمات المفتاحية: الصراع، الحضارة، الصراع الحضاري، التدافع الحضاري، الحوار الحضاري. ;  key words: The clash, the civilization, Civilizational conflict , civilizational scamble,Civilizational Dialogue